2014
DOI: 10.1002/btpr.1928
|View full text |Cite
|
Sign up to set email alerts
|

A novel DAD type and folic acid conjugated fluorescent monomer as a targeting probe for imaging of folate receptor overexpressed cells

Abstract: We describe a modification and post-functionalization technique for a donor-acceptor-donor type monomer; 6-(4,7-bis(2,3-dihydrothieno[3,4-b][1,4]dioxin-5-yl)-2H-benzo[d][1,2, 3]triazol-2-yl)hexan-1-amine. Folic acid was attached to the fluorescent structure. The conjugation was confirmed via NMR and Fourier transform infrared analyses. Cytotoxicity was investigated and the comparison of association of targeted monomeric structures in tumor cells was monitored via fluorescence microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…In 2014, Kanik et al reported a fluorescent probe 38 targeting folic acid receptors. 112 The dye used by the probe forms a donor–acceptor–donor structure to produce fluorescence. After coupling the monomer with folic acid, the probe has good targeting ability for cancer cells (Fig.…”
Section: Fluorescent Probes Targeting Cancer Receptorsmentioning
confidence: 99%
“…In 2014, Kanik et al reported a fluorescent probe 38 targeting folic acid receptors. 112 The dye used by the probe forms a donor–acceptor–donor structure to produce fluorescence. After coupling the monomer with folic acid, the probe has good targeting ability for cancer cells (Fig.…”
Section: Fluorescent Probes Targeting Cancer Receptorsmentioning
confidence: 99%